ANALISIS PERBANDINGAN SPEKTRUM FREKUENSITEMBANG TRADISIONAL SUNDA DENGAN MUSIK KLASIK - Rahmat Hidayat , Muslikhin, dan Dewi Puspitasari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
Sundanese traditional music is a kind of art which exists in West Java created bySundanese society. This music has a power to share with the audiencies. From thefrequency spectrum, this music has fluctuative frequency spectrum like classical music,thus it is interesting to be studied more advanced. This research aims to know thefrequency spectrum analysis of classical music and that of Sundanese traditional music,and the comparison between these two analyses.This research used a representative sample of five musics: they were one music(Symphony 40) and four Sundanese traditional musics (Ewateun, Kiara, Sabilulungan,and Suling Kecapi). From the data, it was found three aspects: 1) the first, middle, andlast frequency, 2) the mean music frequency, and 3) the frequency duration. Those threereferences were used as a comparison of the frequencies of Sundanese traditionalmusic. This analysis was conducted to find the differences, the similarities, and theinference that can be drawn from the differences and the similarities of the frequencyspectrum analysis.The result of this research shows that Sundanese traditional music “Suling Kecapi”has an identical value with classical music (Symphony 40 by Mozart) in the amount of71.34 % based on the frequency domination. The characteristics of the frequency spectrumof “Suling Kecapi” are: a) the amplitudo structure gets higher and little decreases inonsill frequency (20kHz), b) the dominance is in bandwith 4-7kHz, and c) vocal frequency(800-1500Hz) and bass (20-300Hz) is not dominant.Keywords : Sundanese traditional music , classical music, and frequency spectrum